Incidence and concomitant factors of cesarean sections in the bitch: A questionnaire study - Schrank, Magdalena; Contiero, Barbara; Mollo, Antonio (Frontiers in Veterinary Science, 2022)
Dystocia in the canine species is a common problem and elective Cesarean sections (C-sections) have become more frequent in breeds which are at risk. The aim of the present study was to evaluate the incidence of C-section and contributing factors and to compare data on elective and emergency C-section (e.g., regarding stillbirth). Using a questionnaire, a total of 423 bitches of 80 breeds and their 899 litters were included. The mean number of litters per bitch was 2.1 ± 1.1 litters. The overall rate of stillbirth was 6.7%. Of all litters, 194 were born via C-sections (21.6%), of which 35 were declared as elective and 159 as performed due to dystocia. Significantly more C-sections were performed in either small litters (1-2 pups) or large litters (>12 pups) (p<0.001). Bitches which have had prior C-sections had a 4-fold increase in the risk for successive C-sections (RR=4.54 (95%CI 2.56-7.70; p<0.001). Furthermore, primiparous bitches of advanced age had a significantly higher incidence of emergency C-sections (p=0.004). Stillbirth was significantly higher in emergency C-sections compared to elective C-sections (p=0.003). Also timing of intervention had a significant impact on stillbirth in emergency C-sections (p=0.025). Within a breed-specific evaluation significant differences were observed between breeds regarding incidence of C-section and stillbirth. Lesser-known breeds were represented in the population and results have shown that the Norwich Terrier had the highest (51.6%) and the Gordon Setter had the lowest (4.8%) incidence of C-section (p<0.001). The inclusion and evaluation of lesser-known breeds regarding incidence of C-section is of importance as it shows that certain breeds without phenotypical traits such as brachycephaly may also have an increased incidence of emergency C-section and stillbirth. We conclude further that more importance may be given to the age at first parturition concerning the occurrence of dystocia and the decision making regarding possible elective C-sections.